2017
DOI: 10.1177/1040638717727794
|View full text |Cite
|
Sign up to set email alerts
|

Herpesviral infection in a Guiana dolphin (Sotalia guianensis) from the northern coast of Brazil

Abstract: We describe herein herpesvirus-associated genital lesions in a Guiana dolphin ( Sotalia guianensis) from the northern Brazilian coast. Papillary lesions on the vulva, with epithelial hyperplasia, swollen keratinocytes, and intranuclear inclusions, were positive for a herpesvirus ( Gammaherpesvirinae subfamily).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
8
1
Order By: Relevance
“…Cetaceanpoxvirus has been reported in a wide spectrum of hosts, and in Brazil, molecularly confirmed cases are limited to bottlenose dolphins and Guiana dolphins. 55 Herpesvirus has been previously described in 2 Guiana dolphins, 54,62 but infection was not confirmed in the 3 cases tested in this study. The significance of these potential viral coinfections with CeMV is unknown.…”
Section: Discussioncontrasting
confidence: 67%
“…Cetaceanpoxvirus has been reported in a wide spectrum of hosts, and in Brazil, molecularly confirmed cases are limited to bottlenose dolphins and Guiana dolphins. 55 Herpesvirus has been previously described in 2 Guiana dolphins, 54,62 but infection was not confirmed in the 3 cases tested in this study. The significance of these potential viral coinfections with CeMV is unknown.…”
Section: Discussioncontrasting
confidence: 67%
“…The greatest proportions of HV-positive samples in our study occurred in the same tissues in which most previous reports have identified HV in cetaceans: the reproductive system [6,8,9,11,[16][17][18]20,21,23,31,32], the CNS [4,10,15,17,21,23], and the tegument [2,3,[5][6][7]9,15,17,21,22]. The bias that could have arisen owing to the number of samples taken from each system was eliminated by studying the tropism as a proportion over the number of samples analyzed, rather than in absolute numbers (for example, CNS samples were taken from various regions of the same individual).…”
Section: Discussionsupporting
confidence: 52%
“…The presence of lymphoplasmacytic aggregates in the genital submucosa of cetaceans is, within normal limits, considered to be mucosal associated lymphoid tissue (MALT) and is not necessarily indicative of infection [76]. Epithelial hyperplasia is one of the main findings associated with HV in cetaceans, especially in the genital mucosa [8,11,18,23,32,69]. This hyperplasia is often associated with characteristic eosinophilic or amphophilic intranuclear IB [11,18,23,32,69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, alphaherpesvirus has been related to fatal systemic infections [25], lymphoid necrosis [17], interstitial nephritis [18] and encephalitis and meningoencephalitis [26][27][28]. Gammaherpesvirus, however, has been described as mainly associated with mucocutaneous, skin, and genital lesions [16,[29][30][31][32][33], although it has been recently described the first detection of gammaherpesvirus in the central nervous system of several striped dolphins (Stenella coeruleoalba) stranded in the Cantabrian Sea, Spain [34].…”
Section: Introductionmentioning
confidence: 99%